Pelaksanaan Seminar Pola Asuh Anak Usia Dini Pada Era Digital di TK Aisyiyah II Perumnas - Ainun Ainun; Sri Rika Amriani; Nurul Islamiyah (KARYA: Journal of Educational Community Service, 2023)
The community service activity carried out is a PAUD seminar on the topic of early childhood parenting in the digital era. This service program was carried out at Kindergarten Aisyiyah II Perumnas, Makassar City. The seminar participants were 26 people consisting of parents of students, the head of the Karunrung branch of the Kindergarten Aisyiyah II foundation, teachers and 2 students who were carrying out the Teaching Assistance MBKM program at Kindergarten Aisyiyah II Perumnas. This service program aims to provide knowledge to parents about appropriate parenting patterns in the digital era for children. The implementation methods used in this service are presentation, lecture and discussion methods. Next, the data collected was analyzed using the Wilcoxon Test with the help of SPSS, the results of which showed that the data Asymp (2-tailed) = 0.01 < 0.05, meaning that there was a significant difference between participants' understanding before and after being given the PAUD Seminar. The results of the service show that there has been an increase in awareness of parenting patterns, increased understanding of participants, increased parents' understanding of the characteristics of children in the digital era, appropriate parenting patterns in the digital era, strategies for building effective communication with early childhood in the digital era. The research results showed an increase in teacher knowledge after attending the training. The Wilcoxon sign-rank statistical test shows a significant difference between pre-test and post-test scores, indicating an increase in knowledge after training.